Marketing the Sabah Museum in year 2000 / Christopher John Baptist - John Baptist, Christopher (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 1993)
Established 27 years ago, the Sabah Museum has become more public oriented today. It is expected that the Sabah museum to be more dynamic in the strategy to turn Sabah into a fully industrialized nation by the year 2020. Besides, the Sabah Museum is also expected to entertain for the expanding tourist industry. Being mostly Government-funded, the Sabah Museum is entrenched in the Malaysian bureaucratic system. It also appears to have really very little control over its own destiny since its development are governed by other government authorities. This dissertation is marketing the Sabah Museum in the Year 2000 with areas covered on marketing opportunity developing marketing policy, strategy and program. The study provides a comprehensive analysis and guidelines for marketing, as well as outlines the marketing opportunity available for the Sabah Museum. It is expected that with the huge marketing opportunities, the Sabah Museum will change its present objective to profitable sound organization. For the change to occur, however, state and national policy planners must be more understanding and sympathetic towards museum and its needs.